STUDY OF THE APPLICATION AND IMPLEMENTATION OF THERMOELECTRIC REFRIGERATORS (COOLERS) WITH HALF-BRIDGE CONVERTER (Scientific journal of the Fergana State University, 2024)
This article explores the application of thermoelectric coolers based on suitable materials for micromodules and high-efficiency thermoelectric generator systems, and provides an analytical assessment of their implementation.